Development and validation of case‐finding algorithms to identify prosthetic joint infections after total knee arthroplasty in Veterans Health Administration data. Issue 9 (5th July 2021) - Weinstein, Erica J.; Stephens‐Shields, Alisa; Loabile, Bogadi; Yuh, Tiffany; Silibovsky, Randi; Nelson, Charles L.; O'Donnell, Judith A.; Hsieh, Evelyn; Hanberg, Jennifer S.; Akgün, Kathleen M.; Tate, Janet P.; Lo Re, Vincent
Abstract: Purpose: To determine the positive predictive values (PPVs) of ICD‐9, ICD‐10, and current procedural terminology (CPT)‐based diagnostic coding algorithms to identify prosthetic joint infection (PJI) following knee arthroplasty (TKA) within the United States Veterans Health Administration. Methods: We identified patients with: (1) hospital discharge ICD‐9 or ICD‐10 diagnosis of PJI, (2) ICD‐9, ICD‐10, or CPT procedure code for TKA prior to PJI diagnosis, (3) CPT code for knee X‐ray within ±90 days of the PJI diagnosis, and (4) at least 1 CPT code for arthrocentesis, arthrotomy, blood culture, or microbiologic procedure within ±90 days of the PJI diagnosis date. Separate samples of patients identified with the ICD‐9 and ICD‐10‐based PJI diagnoses were obtained, stratified by TKA procedure volume at each medical center. Medical records of sampled patients were reviewed by infectious disease clinicians to adjudicate PJI events. The PPV (95% confidence interval [CI]) for the ICD‐9 and ICD‐10 PJI algorithms were calculated. Results: Among a sample of 80 patients meeting the ICD‐9 PJI algorithm, 60 (PPV 75.0%, [CI 64.1%–84.0%]) had confirmed PJI. Among 80 patients who met the ICD‐10 PJI algorithm, 68 (PPV 85.0%, [CI 75.3%–92.0%]) had a confirmed diagnosis. Conclusions: An algorithm consisting of an ICD‐9 or ICD‐10 PJI diagnosis following a TKA code combined with CPT codes for a knee X‐ray and either a relevant surgical procedure or microbiologic culture yielded a PPV of 75.0% (ICD‐9) and 85.0% (ICD‐10), for confirmed PJI events and could be considered for use in future pharmacoepidemiologic studies.